Hadith #3155 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Ubada bin As-Samit (Sunan Abi Dawud)
Mus’ab b. ‘Umari was killed on the day of Uhud. He had only a striped cloak. When we covered his head with it, his feet appeared, and when we covered his feet, his head appeared. Thereupon the Messenger of Allah (ﷺ) said: Cover his head with it, and cover his feet with some grass.
Grade: Sahih

Hadith #3175 - Sunan Abi Dawud - Abdullah bin Sulaiman عبد الله بن سليمان بن جنادة بن أبي أمية; Hatm bin Isma'il al-Madni حاتم بن إسماعيل المدني; Hisham bin Bhram al-Mda'iny هشام بن بهرام المدائني أبو محمد; Ubada bin As-Samit (Sunan Abi Dawud)
The Prophet (ﷺ) stood up for a funeral (to show respect) and thereafter he sat down.
Grade: Sahih

Hadith #3348 - Sunan Abi Dawud - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Muslim bin Yasar al-'Abbassri مسلم بن يسار البصري - مسلم سكرة المصبح; Qatada قتادة; Salah bin Abi Maryam صالح بن أبي مريم الضبعي - أبو الخليل; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Ubada bin As-Samit (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: Gold for gold is interest unless both hand over on the spot ; wheat for wheat is interest unless both hand over on the spot ; dates for dates is interest unless both hand over on the spot ; barley for barley is interest unless both hand over on the spot.
Grade: Sahih

Hadith #3349 - Sunan Abi Dawud - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Shrahyl bin Aadah, Abu al-Ash'ath شراحيل بن آدة أبو الأشعث الصنعاني; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubada bin As-Samit; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: Gold is to be paid for with gold, raw and coined, silver with silver, raw and coined (in equal weight), wheat with wheat in equal measure, barley with barley in equal measure, dates with dates in equal measure, salt by salt with equal measure; if anyone gives more or asks more, he has dealt in usury. But there is no harm in selling gold for silver and silver (for gold), in unequal weight, payment being made on the spot. Do not sell them if they are to be paid f
Grade: Sahih

Hadith #3415 - Sunan Abi Dawud - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; al-Aswad bin Tha'lbah al-Kndy الأسود بن ثعلبة الكندي الشامي; Ubada bin As-Samit; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
Ibn Rawahah assessed them (the amount of dates) at forty thousand wasqs, and when Ibn Rawahah gave them option, the Jews took the fruits in their possession and twenty thousand wasqs of dates were due from them.
Grade: Sahih

Hadith #3416 - Sunan Abi Dawud - Amr bin 'Uthman عمرو بن عثمان بن عفان; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Junadah bin Abi Umayya; Kathir bin 'Ubaid bin Nmyr كثير بن عبيد بن نمير المذحجي; Ubada bin As-Samit (Sunan Abi Dawud)
I taught some persons of the people of Suffah writing and the Qur’an. A man of them presented to me a bow. I said: It cannot be reckoned property; may I shoot with it in Allah’s path? I must come to the Apostle of of Allah (ﷺ) and ask him (about it). So I came to him and said : Messenger of Allah (ﷺ), one of those whom I have been teaching writing and the Qur’an has presented me a bow, and as it cannot be reckoned property, may I shoot with it in Allah’s path? He said: If you want t
Grade: Sahih

Hadith #4318 - Sunan Abi Dawud - Amr bin al-Aswad al-Ansi عمرو بن الأسود العنسي; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Haywat bin Sharih bin Safwan حيوة بن شريح بن صفوان التجيبي; Junadah bin Abi Umayya; Khalid bin Ma'dan خالد بن معدان; Ubada bin As-Samit (Sunan Abi Dawud)
Every Muslim will read it.
Grade: Sahih

Hadith #4413 - Sunan Abi Dawud - al-Hasan al-Basri الحسن البصري; Htan bin 'Abdullah حطان بن عبد الله الرقاشي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Ubada bin As-Samit; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Qur’anic verse goes: “If any of your woman are guilty of lewdness, take the evidence of four (reliable) witnesses from amongst you against them, and if they testify, Confine them to houses until death do chain them or Allah ordains for them some (other) way. Allah then mentioned man after woman and combined them in another verse : “If two men among you are guilty of lewdness, punish them both. If they repent and amend, leave them alone. This command was abrogated by the verse relating
Grade: Hasan

Hadith #4415 - Sunan Abi Dawud - al-Fadl bin Dlhm al-Wasty الفضل بن دلهم الواسطي ثم البصري القصاب; al-Hasan al-Basri الحسن البصري; al-Rabi' bin Rwh الربيع بن روح; Muhammad bin Awf bin Sufyan محمد بن عوف بن سفيان الطائي; Muhammad bin Khalid bin Muhammad محمد بن خالد بن محمد; Salmah bin al-Mahbaq; Ubada bin As-Samit (Sunan Abi Dawud)
Receive my teachings, receive my teachings. Allah has appointed a way for those women. If the parties have been married, they shall receive a hundred lashes and stoned to death. If the parties are unmarried, they shall receive a hundred lashes and banished for a year.
Grade: Sahih

Hadith #4698 - Sunan Abi Dawud - Ibrahim bin Abi Ablh إبراهيم بن أبي عبلة; Ja'far bin Msafr bin Rashid جعفر بن مسافر بن راشد; Ubada bin As-Samit; Yahya bin Hsan يحيى بن حسان (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to sit among his Companions. A stranger would come and not recognize him (the Prophet) until he asked (about him). So we asked the Messenger of Allah (ﷺ) to make a place where he might take his seat so that when a stranger came, he might recognise him. So we built a terrace of soil on which he would take his seat, and we would sit beside him. He then mentioned something similar to this Hadith saying: A man came, and he described his appearance. He saluted from
Grade: Sahih

Hadith #5016 - Sunan Abi Dawud - Anas ibn Malik; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Qatada قتادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ubada bin As-Samit (Sunan Abi Dawud)
The verse “And the poets it is those straying in evil who follow them. He (Allah) then abrogated it and made an exception saying: Except those who believe and work righteousness, engage much in the remembrance of Allah.”
Grade: Hasan

Hadith #5058 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Junadah bin Abi Umayya; Ubada bin As-Samit; Umayr bin Han'i al-Ansi عمير بن هانئ العنسي (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) went to his bed, he would say: Praise be to Allah Who has given me sufficiency, has guarded me, given me food and drink, been most gracious to me, and given to me most lavishly. Praise be to Allah in every circumstance. O Allah! Lord and King of everything, God of everything, I seek refuge in Thee from Hell.
Grade: Sahih